Both anodal and cathodal transcranial direct current stimulation improves semantic processing. (20th February 2017) - Brückner, Sabrina; Kammer, Thomas
Highlights: tDCS applied to Wernicke's area led to faster RTs in a lexical decision task. The facilitatory effect was observed independent of tDCS polarity. No effect on RTs in a choice reaction time task (motor control) Abstract: Transcranial direct current stimulation (tDCS) is a common method to modulate cortical activity. Anodal tDCS is usually associated with an enhancement of the stimulated brain area, whereas cathodal tDCS is often described as inhibitory brain stimulation method. Our aim was to investigate whether this canonical assumption derived from the motor system could be transferred to the semantic system. Three groups with 20 healthy subjects each were stimulated at Wernicke's area with either anodal, cathodal or sham tDCS. Subsequently, they performed a simple lexical decision task for a duration of about 25 min. Subjects receiving anodal tDCS revealed faster reaction times (RTs) compared to the sham group, although not reaching statistical significance. Surprisingly, in the cathodal group RTs were decreased significantly. All subjects were faster in the second half of the task, but the tDCS-induced improvement lasted for the entire duration of the task. Error rates were not influenced by tDCS, neither were RTs in a choice reaction time task. Thus, both anodal and cathodal tDCS applied to Wernicke's area improved semantic processing. Recently, a meta-analysis revealed that the canonical anodal excitation and cathodal inhibition assumption is observed rarely in cognitive studies. In particular, an inhibitory effect of cathodal tDCS on cognition is rare. Our findings thus support the speculation, that especially language functions could be somewhat 'immune' to cathodal inhibition.